2021
DOI: 10.1080/02670844.2021.1911458
|View full text |Cite
|
Sign up to set email alerts
|

Construction of eco-friendly flame retardant and dripping-resistant coating on polyester fabrics

Abstract: Polyester fabric is widely used in our daily life, while it is highly flammable and easy to produce melt dripping during combustion causing huge potential hazards. Endowing polyester fabric with flame retardancy and dripping-resistance simultaneously is still a difficulty. Eco-friendly polyethylenimine/phytic acid (PEI/PA) coating on polyester fabric was fabricated in this study. The limiting oxygen index value of coated fabric increased from 21.3% of uncoated one to higher than 40%. The dripping phenomenon of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…However, the LOI value of PA/G-15 was still higher than 26% after washing, indicating good durability. This may be due to PEI can react with the free carboxyl group of PET fabric, and it can also react with negatively charged PA [37]. Therefore, this flame retardant coating possessed good washing durability.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the LOI value of PA/G-15 was still higher than 26% after washing, indicating good durability. This may be due to PEI can react with the free carboxyl group of PET fabric, and it can also react with negatively charged PA [37]. Therefore, this flame retardant coating possessed good washing durability.…”
Section: Resultsmentioning
confidence: 99%
“…Phytic acid (PA) is a bio-based phosphorus acid used as the acid source of the IFR coating [34][35][36]. Our previous research reported that the PA/PEI IFR coating was constructed on PET fabrics showing excellent flame retardancy and dripping-resistant properties [37].…”
Section: Introductionmentioning
confidence: 99%
“…During combustion, the stable carbon layer can also block the transmission of heat, oxygen, mass and volatile products [ 40 ]. The commonly used phosphorus-containing polyelectrolytes are ammonium polyphosphate [ 53 , 57 , 58 , 59 , 60 , 61 ], phytic acid [ 56 , 62 , 63 , 64 , 65 , 66 , 67 , 68 ], DNA [ 69 ], phosphatized cellulose [ 70 ], etc. The self-extinguishing effect can be achieved on the phosphorus-containing coating-modified fabric during the burning test.…”
Section: Functionalization Of Lbl Self-assembly Coatings On Fabricsmentioning
confidence: 99%